COVID–19 lockdown effects on the anthropometrics, aerobic capacity, muscle function and metabolic control in children and adolescents with overweight and obesity - Mauricio Inostroza Mondaca; Samuel Silva Garrido; Thais Rodríguez Orellana; Alessandra Maineri Roa; Constanza Olivares Quezada; Cesar Osorio-Fuentealba (Jornal de Pediatria, 2023)
Objective: The lockdown due to a novel coronavirus (COVID–19) pandemic negatively impacted the daily physical activity levels and sedentary behavior of children and adolescents. The purpose of this study was to determine the effects of lockdown on the anthropometric measurements, aerobic capacity, muscle function, lipid profile and glycemic control in overweight and obese children and adolescents. Methods: 104 children and adolescents with overweight and obesity were divided in a non-lockdown group (NL) (n = 48) and a lockdown group (L) (n = 56). Both NL and L groups were evaluated on three consecutive days, day one: anthropometric measurements; day two: aerobic capacity and muscle function and day three: lipid profile and glycemic control. Data are presented as mean ± standard deviation (SD) and median plus interquartile range (IQR) according to their assumption of normality. Results: The L group increased the body weight (81.62 ± 22.04 kg vs 74.04 ± 24.46 kg; p = 0.05), body mass index (32.54 ± 5,49 kg/m2 vs 30.48 ± 6.88 kg/m2; p = 0.04), body mass index by z-score (3.10 ± 0.60 SD vs 2.67 ± 0.85 SD; p = 0.0015), triglycerides [141.00 mg/dl IQR (106.00– 190.00 mg/dl) vs 103.00 mg/dl IQR (78.50– 141.50 mg/dl); p = 0.001], fasting insulin [31.00 mU/L IQR (25.01– 47–17 mU/L vs 21.82 mU/L IQR (16.88 – 33.10 mU/L; p = 0.001)] and HOMA index [6.96 IQR (6.90 – 11.17) vs 4.61 IQR (3.96 – 7.50; p = 0.001)] compared with NL group. Conclusions: The lockdown due COVID–19 pandemic had a negative impact on the anthropometric measurements, lipid profile, and glycemic control of overweight and obese children and adolescents.